2017
DOI: 10.14710/jnc.v6i1.16885
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan usia ibu menikah dini dengan status gizi Balita di Kabupaten Temanggung

Abstract: Latar Belakang : Pernikahan dini (menikah >18 tahun) dapat berpengaruh pada status gizi anak yang dilahirkan. Ibu yang menikah pada usia dini, berisiko memiliki anak berstatus gizi pendek, gizi kurus dan gizi buruk.Tujuan : Penelitian ini bertujuan untuk mengetahui hubungan antara usia ibu menikah dini dengan status gizi batita di Kabupaten Temanggung.Metode :  Penelitian ini termasuk penelitian observasi dengan desain cross-sectional pada 72 anak yang berusia 0-2 tahun dari ibu yang menikah dini dan dipili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 11 publications
(13 reference statements)
0
11
0
12
Order By: Relevance
“…The study found that toddlers with parents who married young were more susceptible to growth and development disorders. (10)(11)(12)(13) Based on maternal income, it appears that there is a very weak relationship between income and the incidence of stunting with r 0.064, where income> 2.5 million is more dominant in causing stunting (64.8%) with data that stunting status is very short, namely 39.8% and short stunting status is 25%. This is different from the research of Aridiyah et al (2015) where the results of the study of mothers who had more stunted children at low economic status in North Maluku.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that toddlers with parents who married young were more susceptible to growth and development disorders. (10)(11)(12)(13) Based on maternal income, it appears that there is a very weak relationship between income and the incidence of stunting with r 0.064, where income> 2.5 million is more dominant in causing stunting (64.8%) with data that stunting status is very short, namely 39.8% and short stunting status is 25%. This is different from the research of Aridiyah et al (2015) where the results of the study of mothers who had more stunted children at low economic status in North Maluku.…”
Section: Discussionmentioning
confidence: 99%
“…Some parents cannot afford to support their children to continue their education so that many teenagers drop out of school. 13 The government has not reviewed the cost of school education to overcome this problem. The government was still trying to improve the quality of education by providing educational facilities and infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…(R10) The teenage marriage occurs before the age of 18 years. 12,13 This case is still high in Banten province both in villages and in urban areas. The number of adolescent pregnancy in rural areas is 13% higher than in urban areas 6%.…”
Section: "Even Though It's Like Sex (Sexual Intercourse) the Calories...mentioning
confidence: 96%
“…Penelitian ini selaras dengan hasil penelitian yang dilakukan oleh Permatasari (2022) di mana ibu yang menikah di usia dini di Puskesmas Kretek 2 Kabupaten Wonosobo tidak berkaitan dengan balita stunting. Demikian pula dengan penelitian Khusna and Nuryanto (2017) pada72 ibu di Kabupaten Temanggung menemukan bahwa tidak ada hubungan antara pernikahan dini pada ibu dengan balita stunting.…”
Section: Gambaran Usia Pernikahan Ibu Pada Balita Stuntingunclassified